Sintering sodium chloride crystals for applications in optically stimulated luminescence (OSL) dosimetry (Brazilian Journal of Radiation Sciences (BJRS), 2022)
The main objective of this work was to study a new technique for the sintering of marine sodium chloride (NaCl) crystals obtained from seawater. In order to obtain an efficient luminescence, a better control in the amount of sample to be used, a better distribution of crystals in every aliquot and verify its applicability as a dosimeter, with dosimetric requirements testing. The common salt is a material that have been already studied in the area of ​​dosimetry, because it has a high sensitivity when exposed to ionizing radiation, therefore can thus be used in luminescent dosimetry. With the purpose of synthesizing the marine crystals with low cost and easy fabrication, we pulverized a concentrated sea salt solution, on 1 cm recycled aluminum discs placed on an oven at 70aºC, with this process we obtained homogeneous aliquots. The salt has a hygroscopic property, we waterproof it using a commercial enamel, in order to inhibit this property. For analyzing the crystalline structure formed with this new technique, we used X-ray diffraction (XRD). For OSL measurements, we use the RISØ TL/OSL reader by blue light stimulation (470 nm) coupled with a beta source, at first, the heat treatment was carried out on the aliquots at 400 ºC, at different times to observe the effect on the OSL signal, irradiated with a dose of 162 mGy, with preheating at 160 °C for 1 s, afterwards we perform a measurement with an assisted temperature of 110 °C for 40 s with blue light. Lastly analyze the dosimetric requirement tests.